Marketing, Existential Malpractice and an Etherised Discipline: A Soteriological Comment. - McDonald, Malcolm (Westburn Publishers, 2002)
This paper reviews the state of marketing theory and practice. A early reviewer of this paper was inclined to "criticise the title on the grounds of obscurity", but concluded it would do as it was. In an academic culture in which the average journal contents page is hardly less obfuscatory, our attempt at irony in the title and introduction seems to have been insufficiently extreme to make our point, which is that marketing academia talks esoterically to itself, even in journals such as this which aim to have a dual practitioner and academic audience. We discuss how this has left consultants as serial fad peddlers, perhaps with more influence but delivering dubious genuine benefit. The result is that marketing practice shows few signs of improving over time. We discuss the vital choices that need to be made in the nature and process of marketing if it is to reach out of its functional silo to seize the heart of the organisation.